Circling the Canon, Volume I : The Selected Book Reviews of Marjorie Perloff, 1969-1994 - Perloff, Marjorie (Book collections on Project MUSE., 2019)
One of our most important contemporary critics, Marjorie Perloff has been a widely published and influential reviewer, especially of poetry and poetics, for over fifty years. Circling the Canon, Volume I covers roughly the first half of Perloff's career, beginning with her first ever review, on Anthony Hecht's The Hard Hours. The reviews in this volume, culled from a wide range of scholarly journals, literary reviews, and national magazines, trace the evolution of poetry in the mid- to late twentieth century as well as the evolution of Perloff as a critic. Many of the authors whose works are reviewed in this volume are major figures, such as W.B. Yeats, Ezra Pound, Sylvia Plath, and Frank O'Hara. Others, including Mona Van Duyn and Richard Hugo, were widely praised in their day but are now all but forgotten. Still others--David Antin, Edward Dorn, or the Language poets--exemplify an avant-garde that was to come into its own.